2013
DOI: 10.1128/aac.00891-13
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Tigecycline in Combination with Colistin, Meropenem, Rifampin, or Gentamicin against KPC-Producing Enterobacteriaceae in a Murine Thigh Infection Model

Abstract: Limited antimicrobials remain active for treating severe infections due to KPC-producing pathogens, and optimal regimens have not been established. In murine thigh infections caused by nine KPC-producing clinical strains of Enterobacteriaceae (meropenem MICs, 1 to 4 g/ml), we evaluated the activities of tigecycline, colistin, meropenem, rifampin, and gentamicin in single and combination regimens lasting for 24 h and 48 h. Rifampin, tigecycline, and gentamicin were the most effective monotherapies, reducing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…The most frequent combination in this study was tigecycline and gentamicin (45 patients, 32 of which also received fosfomycin). Mortality in this group was 20%; interestingly, the combination of tigecycline and gentamicin was more efficacious than each of them combined with colistin and meropenem in a murine model (22).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent combination in this study was tigecycline and gentamicin (45 patients, 32 of which also received fosfomycin). Mortality in this group was 20%; interestingly, the combination of tigecycline and gentamicin was more efficacious than each of them combined with colistin and meropenem in a murine model (22).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show some in vitro synergy in the killing of carbapenemase-producing K. pneumoniae between rifampin and tigecycline or colistin (119,120). However, definitive clinical data are lacking that advocate the routine use of rifampin for the treatment of infections due to carbapenemaseproducing K. pneumoniae.…”
Section: Treatment Of Infections Due To K Pneumoniae With Carbapenemmentioning
confidence: 99%
“…Pournaras et al also showed that MERϩTIG is not synergic in vitro (21). Previous studies of nonlethal and nonsystemic infections were discordant about the antagonistic effects of TIGϩMER in vivo (20,22) and in vitro (23). Further investigation using this combination is required, but we believe that TIGϩMER should be used with caution for treatment of infections due to KPC-producing isolates.…”
mentioning
confidence: 99%